Resisting Arrest: Analysis of Different Prone Body Positions on Time to Stand and Engage : Prone Body Positions and Time to Stand - Sanchez, Kristine; Dawes, J. Jay; Stephenson, Mark; Orr, Robin; Lockie, Robert (NBP. Nauka, bezbednosti, policija, 2023)
An isolated police officer executing an arrest can be placed in a dangerous situation should the subject become non-compliant. Further research is needed to ascertain the position that a subject can be placed in that takes the longest time to rise from the ground. Twenty-four college-aged participants (15 men, 9 women) were recruited for this study. Four prone positions were examined in one session: hands hidden under the chest (PHC); arms perpendicular to the torso and palms of the hand facing up (PPU); arms perpendicular to the torso, palms of the hand facing up, with ankles crossed on the ground (PPUAC); and arms perpendicular to the torso, palms of the hand facing up, with ankles crossed but elevated toward the lower back (PACKB). The order of these positions was randomized amongst participants. Participants were instructed to rise to an athletic position from each position as quickly as possible, with the movements recorded by a video camera. Times were calculated via a frame-by-frame analysis using motion analysis software from movement initiation until participants were standing. A 2 (sex) x 4 (position) repeated measures ANOVA with Bonferroni post hoc calculated between-position differences. There was a significant ANOVA for position (p=0.003) but not sex (p=0.415). The PACKB position was significantly slower than the PHC and PPUAC positions (p≤0.045) and had the slowest movement time to stand (~2.041 s). As reaction time could influence an officer’s safety, the PACKB position required the most time for a subject to stand and potentially engage an officer.
Keywords: apprehension; civilian; detainee; law enforcement